Latin American evangelical theology in the 1970's : the golden decade - Salinas, Daniel. (Religion in the Americas, 2009)
The story of Latin American evangelicals doing theology is mostly unknown. In the 1970s there was an important development with the formation of the Latin American Theological Fraternity (FTL). This group spearheaded the theological production in Latin America, marking the beginning of a critical stage in the history of evangelicals in the region. This book deals with the reception history in North America of the FTL and its program. Interamerican theological dialogue is documented and analysed.